Pengendalian Penyakit Kudis (Diaporthe phaseolorum C&E.) Buah Jeruk Siam (Citrus nobilis L.) Secara Hayati, Nabati dan Mekanik - PANDE WAYAN OKTARDITYA SUDARMA; I MADE SUDANA; NI WAYAN SUNITI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2023)
Utilization of Biologic, Biopesticide and Mechanic to Control Scabies Disease Pathogen (Diaporthe phaseolorum C&E.) Growth on Siam Orange Fruit (Citrus nobilis L.) Siam orange is the main commodity from Bali, more precisely located in Gianyar, Bali. The disease that most attacks the Siam orange is scab caused by Diaporthe phaseolorum. Scab attacks the skin of orange fruits shows symptoms that look like spots, brown to gray, slightly protruding like a cork, and rough texture. Treatment by spraying antagonist agents once a week. The type of antagonist used was 3 antagonist microbes, Balinese spice solution, and mechanical treatment using plastic. Aspergillus aculeatus treatment, namely the use of the fungus Aspergillus aculeatus, was the most effective in suppressing the growth of scabs on Siam orange plants. AL treatment succeeded in suppressing the scab pathogen well. The mean of Aspergillus aculeatus treatment is the smallest in the percentage of disease on tree, which is 60%, and the mean intensity of AL disease is the smallest, which is 28.14%. Control using natural enemies is very influential in suppressing the growth of scab pathogens in siam orange fruit caused by D. phaseolorum. The most effective treatment in suppressing the intensity of pathogenic disease-causing scabs in Siam oranges is AL treatment using the antagonist fungus Aspergillus aculeatus which can suppress the deseases of scab up to 28.14%.